??rteses na marcha de crian??as com paralisia cerebral: estudo cl??nico aleatorizado controlado - Pasini Neto, Hugo (2013)
INTRODUCTION: The main change present in children with CP is the motor impairment. For this, several therapeutic interventions seek to promote the selective motor control, among them the orthoses. Different types of orthotics are used for this purpose, highlighting the use of fixed and articulated orthoses. Whereas the postural insoles aims to reorganize and rearrange mechanical postural muscle tone, that may play a role similar to the conventional orthoses. OBJECTIVE: To evaluate and compare different types of orthoses on gait of children with cerebral palsy. METHODS: a systematic review of the literature considering the following inclusion criteria was done: (1) design: a controlled clinical trial, (2) population: children and adolescents with cerebral palsy (3) Intervention: rigid or articulated orthoses, (4 ) outcome: improvement in motor function and gait performance. Next, we conducted a randomized controlled double blind in which after meeting the legal aspects and the eligibility criteria, 10 children between 4 and 12 years old were randomly divided into a control group (12) and experimental group (12). Children in the control group used the placebo insole and children in the experimental group used postural insoles. These insoles were made in ethylene vinyl acetate, which in the case of postural insoles, received thermoforming to fasten the foot problems related to postural correction and in the case of placebos insoles did not receive the correct parts. In relation to evaluation, this was composed of three-dimensional gait analysis and it was performed before, immediately after, 3 months later and 1 month without application of insoles. This evaluation was performed using the SMART-D 140 ?? - BTS Engineering with eight cameras and were considered for statistical analysis the temporal parameters of gait. Data analysis considered the adherence to the bell curve, by Kolmogorov-Smirnov and how they were presented parametric, were expressed as mean (standard deviation or confidence interval of 95%). For intergroup analysis it was used the independent t test and intragroup analysis was used repeated measures ANOVA. RESULTS: In the systematic review, seven controlled studies comparing the effect of orthoses fixed and articulated were found and they showed different therapeutic indications to each one. In relation to the immediate effect of postural insoles it is possible to observe a significant increase in parameters related to gait velocity and cadence in children in the experimental group compared to control group. CONCLUSION: Considering this preliminary phase of this study, it was observed that children classified as level I and II of the GMFCS scale showing small spasticity and muscle contracture benefit more of orthoses that favor function since these allow greater freedom associated with functional stimuli correctives.